IEEE Electric Ship Technologies Symposium, 2005. 2005
DOI: 10.1109/ests.2005.1524644
|View full text |Cite
|
Sign up to set email alerts
|

The electric ship integration initiative - an overview

Abstract: Abstrucr-An initiative for Robust Control and Reconfiguration o f Shipboard EIectric Power Systems is underway that combines long-term research and education objectives. The Electric Ship Initiation Initiative (ESIf) team brings together the programs and resources of leading electric power research institutions to develop near-to midterm electric ship concepts. Specific focus on the development and implementation of a new educational curriculum l o r scientists, engineers and naval officers provides an essenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Furthermore, the breaking of DC fault currents has always been very difficult, although research into electro-mechanical hybrid and solidstate current interruption has shown promising results [12]. Papers [4] and [5] suggest the use of a hybrid IFEP power system ( Fig. 4.…”
Section: Hybrid Architecturementioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the breaking of DC fault currents has always been very difficult, although research into electro-mechanical hybrid and solidstate current interruption has shown promising results [12]. Papers [4] and [5] suggest the use of a hybrid IFEP power system ( Fig. 4.…”
Section: Hybrid Architecturementioning
confidence: 99%
“…Within the marine community there has been a debate for some time regarding DC versus AC power distribution systems [3], [4], [5], [8], [9]. The use of DC distribution offers certain advantages over AC distribution such as higher power transfers for similar voltages, unity power factor, no frequency synchronization for connecting ac systems coupled via a DC bus, no AC noise coupling, etc.…”
Section: Hybrid Architecturementioning
confidence: 99%
See 1 more Smart Citation
“…Compared to two-level inverters, multilevel inverters excel in nearly all the performance indexes. Therefore, they are particularly suited for high-power rating large vehicular motor drives (> 250 kW) [7], [17]- [20], where the added power switch cost is less of a concern. Multilevel converters achieve much lower output harmonic distortion with less switching stress and reduce or eliminate the need for passive filtering devices.…”
Section: Introductionmentioning
confidence: 99%
“…Among these large vehicles, the series powertrain topology is dominantly used and the propulsion motor and inverter are rated for the full vehicle power. Therefore, applications of multilevel converters in large vehicles are receiving considerable research interest [7], [17]- [20].…”
Section: Introductionmentioning
confidence: 99%